2009
DOI: 10.1016/j.jdermsci.2009.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal photochemotherapy

Abstract: Although extracorporeal photochemotherapy (ECP) is reported to be effective for a wide variety of diseases, such as cutaneous T cell lymphoma, autoimmune diseases, organ graft rejection, and graft versus host disease, its mechanism of action remains unclear. The basis of extracorporeal photopheresis is the reinfusion of leukocytes previously exposed to 8-methoxypsoralen (8-MOP) and ultraviolet A radiation. Although only 5-10% of circulating mononuclear cells is treated during one ECP procedure, the treatment h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Advantages of ECP include the low rates of infectious complications and virus reactivation compared with other treatment modalities, such as anti‐thymocyte globulin or monoclonal antibodies (e.g., basiliximab, etanercept, infliximab) . Although the exact mechanism of action has not yet been fully elucidated, it has been shown that ECP induces apoptosis in treated lymphocytes, especially in alloreactive T cells, which actively proliferate during GVHD, having a higher susceptibility to apoptosis than resting cells . In contrast to systemic immunosuppressants, ECP has immunomodulatory effects, including expansion of regulatory T cells, modulation of cytokine production, and maturation of dendritic cells …”
mentioning
confidence: 99%
“…Advantages of ECP include the low rates of infectious complications and virus reactivation compared with other treatment modalities, such as anti‐thymocyte globulin or monoclonal antibodies (e.g., basiliximab, etanercept, infliximab) . Although the exact mechanism of action has not yet been fully elucidated, it has been shown that ECP induces apoptosis in treated lymphocytes, especially in alloreactive T cells, which actively proliferate during GVHD, having a higher susceptibility to apoptosis than resting cells . In contrast to systemic immunosuppressants, ECP has immunomodulatory effects, including expansion of regulatory T cells, modulation of cytokine production, and maturation of dendritic cells …”
mentioning
confidence: 99%
“…ECP involves the induction of apoptosis in treated lymphocytes; alloreactive T cells, which actively proliferate during GVHD, have higher susceptibility to apoptosis than resting lymphocytes . ECP, moreover, induces tolerogenic dendritic cells that stimulate a Th2 rather than Th1 response and, after the phagocytosis of apoptotic T cells, gives rise to a clonotypic immune reaction and leads to tolerance …”
mentioning
confidence: 99%
“…One such candidate is administration by pheresis. Among the various types of pheresis, extracorporeal photopheresis (ECP) is well known to have therapeutic potential in transplant rejections, especially in cases of cardiac transplant rejection [74] . ECP has been reported to affect peripheral blood monocytes, resulting in the induction of Treg and the development of immunological tolerance [75,76] .…”
Section: Resultsmentioning
confidence: 99%